Implementation of Non-Refoulement Principles in Legislation as Protection of Refugees in Indonesia - Dermawan, Kayla Daffanya Putri; Diani Sadiawati (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This article is about the implementation of the principles of non-refoulement related to refugee protection in Indonesia, the problem is that Indonesia still has not ratified the 1951 convention and the 1967 additional protocol, this has an impact on refugees who come to Indonesia. The purpose of this article is to see how the implementation of the principles of non-refoulement in Indonesian legislation, then to analyze the challenges and dynamics of refugees in Indonesia. The method used in this article is normative method, the type of analysis used is qualitative, the type of this article is library research. Then the results of this article found that the complexity of global problems related to refugees requires serious attention from the international community. Although Indonesia has not ratified the 1951 Convention and 1967 Protocol, the commitment to protect and assist refugees remains a focus to fulfill international responsibilities. The principle of non-refoulement is one of the foundations of refugee protection that prohibits forced return. Although Indonesia already has a national legal framework related to refugee protection, the implementation of the principle of non-refoulement needs to be analyzed more deeply. This article is important because it provides a deeper understanding of the challenges and steps that can be taken to improve refugee protection in Indonesia. This paper fills the knowledge gap regarding the implementation of the principle of non-refoulement in Indonesia and is expected to provide suggestions and recommendations to improve the protection and implementation of the principle of non-refoulement of refugees in Indonesia.